Current Progress and Perspectives on Using Gold Compounds for the Modulation of Tumor Cell Metabolism - Kou, Leiya; Wei, Shuang; Kou, Pei (Frontiers in Chemistry, 2021)
Altered cellular metabolism, which is essential for the growth and survival of tumor cells in a specific microenvironment, is one of the hallmarks of cancer. Among the most significant changes in the metabolic pattern of tumor cells is the shift from oxidative phosphorylation to aerobic glycolysis for glucose utilization. Tumor cells also exhibit changes in patterns of protein and nucleic acid metabolism. Recently, gold compounds have been shown to target several metabolic pathways and a number of metabolites in tumor cells. In this review, we summarize how gold compounds modulate glucose, protein, and nucleic acid metabolism in tumor cells, resulting in anti-tumor effects. We also discuss the rationale underlying the anti-tumor effects of these gold compounds and highlight how to effectively utilize against various types of tumors.